Peramalan (Forecasting) Jumlah Kunjungan Pasien Di Klinik Kasih Ibu Menggunakan Metode Weight Moving Average - Zanma Ameta Tarigan; Jijon Raphita Sagala (Jurnal Media Informatika, 2021)
Kasih Ibu Clinic is a small public health facility that was established to provide services to the communitKasih Ibu Clinic is a small public health facility that was established to provide services to the community, especially those in Jaharun B Village, hamlet 1, Kec. Galang. The problem that is often experienced by the Kasih Ibu clinic is the difficulty in preparing and planning because of the erratic number of patient visits. This research is a forecasting or forecasting using the weight moving average method with a period of 3 months. The weight moving average method uses the number of moving averages that are given different weights for each data based on the most recent or most recent data. This study aims to build a system that helps the clinic in predicting the number of patient visits in the future, so that it can anticipate a shortage of supporting resources, minimize the occurrence of excess inventory and can provide the best service for every patient who comes for treatment at the clinic.